Otimização da coleção de periódicos da Biblioteca de Veterinaria da Universidade Federal Fluminense - Folly, Eneyda de Mattos (1976)
As the number and cost of the scientific journals increase every day, it’s not economic obtain 100 por cento of those whihc cover a specific subject, mainly if the library can count on the support of information network Citations given in papers that were written by authors from Faculdade de VEterinária da UniversidadeFederal Fluminense, citations given by Brazilian authors in articles on veterinary medicine published in 23 national journals and request froms of scientific articles zerox were examined oin order to obtain the data to optimize the journal collection of the Biblioteca de Veterinária da Universidade Federal Fluminense The journals were listed according to its rate of use and the selected ones for the present estimation were those responsible for 50 por cento of the citations given in papers that were writtenm by authors above mentioned and those asked to be xeroxed aight or more times As the Biblioteca de VEterinária da Unviersidade Federal Fluminense is as multidisciplinary one and it serves a developping Collenge, no cutting down was made on account of obsolescenge. The solution was a less P and by the mantainance of them without cut due to obsolescence.